Analisis Budaya Organisasi Pada Bisnis Internasional Perusahaan Alibaba - Verliana Elzagi; Fernanda Yeronica; Hellena Risvi; Melissa Melissa; Hendy Williyan; Antony Sentoso (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The Alibaba Group has become a global e-commerce powerhouse with a diverse and extensive business portfolio. As Alibaba expands its reach internationally, the company will encounter diverse cultures, social norms, and business practices. Therefore, a well-structured organizational framework is needed, along with conducting analyses using Hofstede and Trompenaars frameworks, to help manage challenges in a multicultural company. The research method employed is qualitative data analysis using literature reviews for data collection. The analysis results indicate that Alibaba implements a complex organizational structure. Additionally, analyses based on Hofstede, Trompenaars, and corporate cultural types at Alibaba reveal the prominent influence of Chinese culture. However, Alibaba has successfully integrated diverse values, norms, and cultural practices from various countries where they operate. Alibaba can leverage cultural diversity within the organization as a key driver for innovation, global growth, and competitive advantage in today's increasingly interconnected market.